2015
DOI: 10.1039/c4cp05303f
|View full text |Cite
|
Sign up to set email alerts
|

Proton irradiation of DNA nucleosides in the gas phase

Abstract: The four DNA nucleosides guanosine, adenosine, cytidine and thymidine have been produced in the gas phase by a laser thermal desorption source, and irradiated by a beam of protons with 5 keV kinetic energy. The molecular ions as well as energetic neutrals formed have been analyzed by mass spectrometry in order to shed light on the ionization and fragmentation processes triggered by proton collision. A range of 8-20 eV has been estimated for the binding energy of the electron captured by the proton. Glycosidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 70 publications
1
55
0
Order By: Relevance
“…We have previously reported mass spectra for each of the nucleosides using one-colour (1+1) resonanceenhanced multiphoton ionization (REMPI) at 267 nm with low interaction intensity (see supplementary material in reference [43]). These show that parent molecular ions make up more than 90% of the ion yield for thymidine and adenosine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported mass spectra for each of the nucleosides using one-colour (1+1) resonanceenhanced multiphoton ionization (REMPI) at 267 nm with low interaction intensity (see supplementary material in reference [43]). These show that parent molecular ions make up more than 90% of the ion yield for thymidine and adenosine.…”
Section: Resultsmentioning
confidence: 99%
“…To produce gas-phase targets, nucleosides were desorbed directly from solid samples deposited on a 10 µm stainless steel foil which was integrated into the repeller electrode of a time-of-flight mass spectrometer [42] [43]. The samples (99% purity) were obtained from Sigma-Aldrich and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intact, isolated, and neutral molecules were produced by irradiating the reverse side of the foil with a continuous wave diode laser. The exact temperature of the desorbed molecules is hard to determine accurately, but previous measurements taken under similar desorption conditions have shown that there is no fragmentation of any of the molecules prior to the interaction with the laser pulses [8] [33].…”
Section: Methodsmentioning
confidence: 99%
“…Also due to the size and di culty of isolation, measurements are currently limited with respect to biological molecules in their native (aqueous) environment. Currently most of our understanding comes from studies in the gas phase, where the e↵ects of proton and other ion collisions on small molecules have been investigated [5,8,[33][34][35][36][37][38][39][40][41]. The resulting fragments can then be used to determine the most common fragmentation channels for a given particle energy.…”
Section: Introductionmentioning
confidence: 99%